Chloride channels - Guggino, William B. (Current topics in membranes, 1994)
The amount of new information on the molecular biology of chloride channels has grown tremendously in recent years. This large amount of information gives some unique and, in some instances, surprising insights into the function and structure of chloride channels which are present in every cell. This volume contains a series of in-depth reviews of chloride channel physiology, biophysics, and molecular biology. The reviews cover chloride channels found in the plasma membrane as well as in organelles of both plant and animal cells.